PERAN MEDIASI KEPUASAN KERJA PADA PENGARUH BUDAYA ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASI - Maria Juni Wati; Uju Suji’ah (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the mediating role of job satisfaction on the influence of organizational culture and career development on organizational commitment. The number of samples is 85 employees with saturated sampling technique. Data collection method with questionnaire. Data testing with validity test, reliability test, classical assumption test, multiple linear regression test, determination coefficient test (adjusted R2), partial significance test (t test), simultaneous significance test (f test), and mediation test (sobel test). The results of the study indicate that: 1). Partial significance test: organizational culture has a positive and insignificant effect on organizational commitment; Career development has a positive and significant effect on organizational commitment; Organizational culture has a positive and significant effect on job satisfaction; Career development has a positive and significant effect on job satisfaction; Job satisfaction has a positive and significant effect on organizational commitment; 2). Simultaneous significance test: organizational culture and career development have a positive and significant effect on organizational commitment; Organizational culture and career development have a positive and significant effect on job satisfaction; 3). Mediation test: job satisfaction is able to mediate organizational culture on organizational commitment; Job satisfaction is able to mediate career development on organizational commitment